PENINGKATAN NILAI EKONOMIS PRODUK AYAM BURAS DI DESA PULUKAN KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA - I GST. PT. JAMASUTA; K. SULANDRA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2006)
ABSTRACT The native chicken farmers at Pulukan Village has low income from their chicken husbandry, because the farmers sold their products in the natural form. In order increase their profit, the farmers are suggested to sell their products in the processed form. The farmers did not know how to process all the chicken products. In this activity the team of the community service transferred to the farmers some information and practical work about chicken products technology i.e. salted eggs, ?bekasem? eggs, ?lab-lab-nyah? eggs, smoked chicken, ?betutu? chicken and ?bekakak? chiken. The activity results that the farmers were able to treat and process their chicken products.